2019
DOI: 10.1002/lary.28281
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of iatrogenic and idiopathic vocal fold paralysis may be distinct

Abstract: Objective: Spontaneous vocal recovery from idiopathic vocal fold paralysis (VFP) appears to differ in time course from recovery in iatrogenic VFP. This study aimed to determine if this difference could be explained by differing mechanisms causing recurrent laryngeal nerve (RLN) dysfunction, specifically whether idiopathic VFP is consistent with a focal RLN axonal lesion.Study Design: Case series with mathematical modeling.Methods: A review of 1267 cases of unilateral VFP over a 10-year period yielded 114 subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Pei et al postulated that a significant number of instances of IVCP may be attributed to neuritis affecting the segment of vagus nerve situated proximal to the point at which the SLN branches off. 4 However, the absence of disparity between leftsided and right-sided paralysis in IVCP involving SLN aligns with the hypothesis posited by Mau et al 8 This hypothesis suggests that an equal number of patients with combined RLN and SLN involvement on both sides of IVCP implies a pathophysiological cause that occurs symmetrically and affects a location proximal to the bifurcation of RLN and SLN. 19…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Pei et al postulated that a significant number of instances of IVCP may be attributed to neuritis affecting the segment of vagus nerve situated proximal to the point at which the SLN branches off. 4 However, the absence of disparity between leftsided and right-sided paralysis in IVCP involving SLN aligns with the hypothesis posited by Mau et al 8 This hypothesis suggests that an equal number of patients with combined RLN and SLN involvement on both sides of IVCP implies a pathophysiological cause that occurs symmetrically and affects a location proximal to the bifurcation of RLN and SLN. 19…”
Section: Discussionsupporting
confidence: 78%
“…The involvement of SLN and CM in IVCP is a topic of interest. Mau's research revealed a significantly higher occurrence of simultaneous CM involvement in IVCP cases compared to iatrogenic cases 8 . Additionally, Chang et al's quantitative LEMG analysis demonstrated that 53% of IVCP patients exhibited concurrent deficits in the RLN and SLN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although certain vocal behaviors or vocal fold anatomic features may predispose to particular lesions, the actual development of these lesions and their recurrence are randomly determined processes aptly studied via stochastic models. Stochastic models have been previously applied in laryngology to elucidate the physiology of recovery from vocal fold paralysis, 20,21 and such an approach may offer novel insights into the genesis of phonotraumatic lesions.…”
Section: Introductionmentioning
confidence: 99%
“…The frequency of VFMI in patients without a prior at-risk operation is surprising at almost 1 in 5 patients (19%), and suggests a possible congenital etiology. 30,31 Given the prevalence of VFMI in our patient population and the poor discriminatory nature of relying on symptoms alone, we recommend a strategy of routine screening of all patients at risk, regardless of symptoms or prior surgical history.…”
Section: Discussionmentioning
confidence: 99%